PERCEPTION OF LIFE QUALITY OF VISUAL DISABLED ATHLETES (Fiep Bulletin - online, 2020)
Abstract: People with visual impairment make up a group vulnerable to worse perception of Quality of Life due to limitations related to vision loss. In this scenario, actions that can promote a better quality of life for these people are needed. Among them, sports is a possibility. Objective: To investigate the quality of life of athletes with visually impaired goalball players. Study Design: A cross-sectional study was conducted with 16 goalball athletes. Quality of life was assessed using the WHOQOL-BREF (1997) questionnaire, which assessed the following domains: physical, psychological, social relations, environment, and two general questions about quality of life. The higher the score, the higher the satisfaction. Results: It was observed that the social relations domain had the highest level of satisfaction, since the average found was 16.7 and the highest observed value was the maximum value 20.0. In contrast, the environmental domain had the lowest level of satisfaction, as its average score was 12.8 and none of the respondents had the highest score. Final Considerations: It is considered that visually impaired athletes who practice goalball present greater satisfaction in the “social relations” domain of Quality of Life and, at the other extreme, greater dissatisfaction in the “environment” domain. These results show that sports practice is positive to improve the interpersonal relationship of visually impaired people, as it allows, in a way, more people with the same disability to relate. Regarding dissatisfaction with the environment, this result reinforces that unfortunately the accessibility conditions for people with disabilities are still precarious, limiting their daily activities.